Pengaruh High Intensity Interval Training (HIIT) terhadap Persentase Lemak Tubuh Wanita Menopause Penderita Obesitas - Muarif Arhas Putra; Rahmi Fitria; Rahmah Evita Putri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The purpose of this study was to determine the effect of high intensity interval training (HIIT) on the body fat percentage of menopausal women with obesity. This research method was quasi-experimental. The research design carried out was the pretest-posttest nonequivalent control group design. The results obtained before and after the treatment were both normally distributed and homogeneous. Then independet sample t-test carried out with the result that there was significant difference between the control and experimental groups. In conclusion, high intensity interval training (HIIT) had a significant impact on the fat percentage of menopausal women with obesity. Keywords: HIIT, Obesity, Menopause.